Religiositas Suku Biak dalam Lagu Rakyat Wampasi Wambarek: Religiosity Etnics Biak in Wampasi Wambarek Folksong - Ummu Fatimah Ria Lestari (Balai Bahasa Provinsi Papua, 2019)
This study discusses the religiosity of Biak people in the folklore songs Biak Wampasi Wambarek. Religiosity is defined as devotion to religion or piety. Simply put, this religiosity is defined as a religious life. Religiosity is also interpreted as a good attitude, praiseworthy, and straight in accordance with religious values. Song or song in Biak tribe is something important, because the song is an integral part of the wor (ceremonial). The song is considered as a medium for delivering the intent and purpose of the wor. In addition to dance, the song is also a proof of the greatness of a family or clan in holding wor. The approach used in the research through semiotic approach, namely the analysis of signs. A semiotic approach is used to identify sign conventions that show the unity of the meaning of a literary work. The method of this research is analytic descriptive. Data were collected through library research. The data collection technique used is the reading technique. The data analysis steps taken to achieve the objectives of this research are translation, heuristic readings, hermeneutical readings, and semiotic readings of the song array. After analyzing the folk songs Biak Wampasi Wambarek through several processes, it can be concluded that this song line revealed the religiosity of Biak people. The form of religiosity is seen in a line that praises the greatness of God Almighty and grateful for His grace. In this folk song, the word 'God' or the word meaning 'the Creator' is not mentioned implicitly. However, it does not mean that the lines in this song do not praise the Lord.